Conflict Management among Clinical Nurses - N Dehghan nayeri; R Negarandeh; N Bahrani; A Sadoghi Asl (Tehran University of Medical Sciences, 2010)
Background & Objective: Conflict occurs more frequently in health care organizations than the other settings due to complexity, frequent interaction between personnel, variations in specialties, roles, and hierarchy. Although conflict is not harmful and destructive in its nature; and some degrees of conflict can help to improve health care services, high levels of conflict or its continuity may be harmful. Therefore, it is necessary to manage and control conflict. This study was carried out to assess the relationship between components of the conflict control model. Methods & Materials: In this cross-sectional study, we developed a questionnaire that probed the relationships between components of conflict control model. A total of 290 nurses were recruited to the study using multi-stage sampling procedure from general educational hospitals in Tehran. Data were gathered using a questionnaire. Content validity of the questionnaire was examined by the expert panel. The internal consistency of the questionnaire was 0.81. Data were analyzed in the SPSS using descriptive statistics and spearman statistical test. Results: The range of age was 22-53 (34.5±8.2). The majority of the respondents (88.6%) were female, 57.6% were married; and 84.8% were staff nurses. From the majority of nurses' perspective, the meaning of conflict was discoordination, disagreement and disparity. However, some of the nurses meant it as violence, and difficult issues. About 41.4% of the respondents used negotiation, when they faced up to conflict. Other strategies were aggression, disagreement, avoidance, forgiveness, ignorance, and imposing own ideas to the others. From the respondents' point of view, factors that might cause or control the conflict were "mutual understanding and interaction" (32.4%), personality of nurses and their individual characteristics (26.6%), and conditions of the job (21.7%). Interaction was recognized to be the core strategy in conflict control model. Interaction had also significant associations with the five main variables in this study. Conclusion: Lack of appropriate and efficient communication was an important factor in occurrence of conflict from the nurses' point of view. It is essential to improve nurses' and managers' communication channels by helping personnel to use effective communication skills. This measurement can be helpful for staff in understanding each other and reducing misconceptions. In addition, recognizing additional factors and variables that increases the occurrence of conflict can help to modify effective approaches.